Phenylpropanoid amides from Solanum rostratum and their phytotoxic activities against Arabidopsis thaliana - Liu, Zhixiang; Ma, Xiaoqing; Zhang, Nan; Yuan, Linlin; Yin, Hongrui; Zhang, Lingling; An, Tong; Xu, Yubin (Frontiers in Plant Science, 2023)
Introduction Solanum rostratum, an annual malignant weed, has seriously damaged the ecological environment and biodiversity of invasion area. This alien plant gains a competitive advantage by producing some new phytotoxic substances to inhibit the growth of native plants, thus achieving successful invasion. However, the chemical structures, inhibitory functions and action mechanisms of phytotoxic substances of S. rostratum remain unclear. Methods In this study, to clarify the chemical structures of phytotoxic substances from S. rostratum, we isolated phenylpropanoid amides from the plant. Their structures were identified by comprehensive HR-ESIMS, NMR and ECD data. And the inhibitory functions of isolated phenylpropanoid amides on one model plant (Arabidopsis thaliana) were also investigated. In addition, the action mechanisms of active phenylpropanoid amides were revealed by antioxidant-related enzymes [Catalase (CAT), Peroxidase (POD), Superoxide dismutase (SOD)] activities and corresponding molecular docking analyses. Results and Discussion Phytochemical research on the whole plant of S. rostratum led to the isolation and identification of four new phenylpropanoid amides (1−4), together with two known analogues (5−6). All the compounds showed phytotoxic effects with varying levels on the seed germination and root elongation of one model plant (Arabidopsis thaliana), especially compound 2 and 4. Likewise, compounds 2 and 4 displayed potent inhibitory effects on antioxidant-related enzyme (POD). In addition, compounds 2 and 4 formed common conventional hydrogen bonds with residues Ala34 and Ser35 in POD revealed by molecular docking analyses. These findings not only helped to reveal the invasion mechanism of S. rostratum from the perspective of “novel weapons hypothesis”, but also opened up new ways for the exploitation and utilization of S. rostratum.